Preliminary physician and pharmacist survey of the National Health Insurance PharmaCloud system in Taiwan. (October 2017) - Tseng, Yu-Ting; Chang, Elizabeth H.; Kuo, Li-Na; Shen, Wan-Chen; Bai, Kuan-Jen; Wang, Chih-Chi; Chen, Hsiang-Yin
Highlights: The preliminary study results indicated a moderate satisfaction toward Taiwan PharmaCloud system. Hospital pharmacists had a high satisfaction rate, but neither are physicians and community pharmacists. Related policies, promotion activities, and standardization processes, including privacy protection, should be established to make the Taiwan PharmaCloud system a convenient platform to facilitate medication reconciliation in the future. Abstract: Background: The PharmaCloud system, a cloud-based medication system, was launched by the Taiwan National Health Insurance Administration (NHIA) in 2013 to integrate patients' medication lists among different medical institutions. The aim of the preliminary study was to evaluate satisfaction with this system among physicians and pharmacists at the early stage of system implementation. Methods: A questionnaire was developed through a review of the literature and discussion in 6 focus groups to understand the level of satisfaction, attitudes, and intentions of physicians and pharmacists using the PharmaCloud system. It was then administered nationally in Taiwan in July to September 2015. Descriptive statistics and multiple regression were performed to identify variables influencing satisfaction and intention to use the system. Results: In total, 895 pharmacist and 105 physician questionnaires were valid for analysis. The results showed that satisfaction with system quality warranted improvement. Positive attitudes toward medication reconciliation among physicians and pharmacists, which were significant predictors of the intention to use the system (β= 0.223, p  < 0.001). Most physicians and pharmacists agreed that obtaining signed patient consent was needed but preferred that it be conducted by the NHIA rather than by individual medical institutions (4.02 ± 1.19 vs. 3.49 ± 1.40, p  < 0.01). Conclusions: The preliminary study results indicated a moderate satisfaction toward the PharmaCloud system. Hospital pharmacists had a high satisfaction rate, but neither are physicians and community pharmacists. Continuously improvement on system quality has been performing based on the results of this preliminary survey. Policies and standardization processes, including privacy protection, are still warranted further actions to make the Taiwan PharmaCloud system a convenient platform for medication reconciliation.